Modelling compliance with antihypertensives and statins in Ireland, using a national prescription claims database - Fitz-Simon, Alexandra Nicola O'Connell (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2006)
Hypertension and high cholesterol, especially in the middle-aged and elderly, are fairly common, and pharmacological therapy is often required to control them. In spite of substantial knowledge of the consequences of uncontrolled blood pressure and high cholesterol (for example cardiovascular and cerebrovascular disease) and the proven benefits of treatment for these conditions, many patients continue to have uncontrolled blood pressure and cholesterol levels. It has been demonstrated in large clinical trials that treatment wth appropriate therapies substantially reduces the risk of morbidity and mortality. While lack of compliance is by no means the only reason for low control rates, many patients prescribed antihypertensives or lipid-lowering therapies do not continue to take them and therefore do not benefit. Previous studies of compliance have often not used the most appropriate methods to analyse drug discontinuations and thus have not been able to explore fully various characteristics of the problem- in particular the patterns of prescription claiming at the individual level, and their longitudinal dependencies. Determining appropriate models for the analysis of discontinuation and switching of statins and antihypertensives in the Irish population may help clinicians making decisions about what and how to prescribe.
Keywords: Pharmacology and Therapeutics, Ph.D.; Ph.D. Trinity College Dublin